Analysis of surgical interruption of the enterohepatic circulation as a treatment for pediatric cholestasis - Wang, Kasper S. (Hepatology, 2017)
To evaluate the efficacy of non-transplant surgery for pediatric cholestasis, 58 clinically diagnosed children, including 20 Alagille syndrome (ALGS), 16 Familial Intrahepatic Cholestasis-1 (FIC1), 18 Bile Salt Export Pump (BSEP) disease, & 4 others with low γ-glutamyl transpeptidase disease (levels <100 U/L), were identified across 14 Childhood Liver Disease Research Network (ChiLDReN) centers. Data were collected retrospectively from individuals who collectively had 39 partial external biliary diversions (PEBD), 11 ileal exclusions (IE) and 7 gallbladder-to-colon diversion (GBC). Serum total bilirubin decreased after PEBD in FIC1 (8.1±4.0 vs. 2.9±4.1 mg/dL, preop vs. 12–24 months postop respectively, p=0.02) but not in ALGS or BSEP. Total serum cholesterol decreased after PEBD in ALGS patients (695±465 vs. 457±319 mg/dL; preop vs. 12–24 months postop respectively; p=0.0001). Alanine aminotransferase levels increased in ALGS after PEBD (182±70 vs. 260±73 IU/L, preop vs. 24 mos. p=0.03) but not in FIC1 or BSEP. ALGS, FIC1, and BSEP patients experienced less severely scored pruritus after PEBD (ALGS: 100% vs. 9% severe, FIC1: 64% vs. 10%; BSEP: 50% vs. 20%, preop vs. >24 mos. postop respectively, p<0.001). ALGS patients experienced a trend toward greater freedom from xanthomata after PEBD. There was a trend toward decreased pruritus in FIC1 after IE and GBC. Vitamin K supplementation increased in ALGS after PEBD (33% vs. 77%, p=0.03. Overall, there were 15 major complications after surgery. 12 patients (3 ALGS, 3 FIC1, 6 BSEP) subsequently underwent liver transplantation. CONCLUSION: This is the first multi-center analysis of non-transplant surgical approaches to intrahepatic cholestasis. Approaches vary, are well tolerated, and generally although not uniformly result in improvement of pruritus and cholestasis.